2022
DOI: 10.3390/agriculture12101690
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Insect Pollination and Biochar Seed Coating on Okra (Abelmoschus esculentus) Seed Quality at Varying Temperature Conditions

Abstract: Underutilized crops, such as okra, have the potential to alleviate stress on crop production imposed by climate change and farming conditions, but their production is greatly hindered by poor seed quality. Insect pollination and seed coating with organic substances (biochar) may improve okra’s seed performance, but the beneficial effects of biochar seed coating and pollination on the seed quality of okra grown under stressful conditions is unknown. We examined the impact of pollination and biochar seed coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…It has been well documented that biochar exhibits strong moisture uptake and retention properties, mainly attributed to its large, specific surface area and highly porous structure [12,26]. A similar finding was reported by Adelabu and Franke [13], where biochar coating blends had a substantial and positive impact on germination, seedling elongation, and fresh biomass in okra. They hypothesized that since biochar is a carbonaceous organic matter and a source of abundant nutrients, it could result in an increase in plant growth and biomass accumulation by supplying rich nutrition to the seedling embryo during emergence.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has been well documented that biochar exhibits strong moisture uptake and retention properties, mainly attributed to its large, specific surface area and highly porous structure [12,26]. A similar finding was reported by Adelabu and Franke [13], where biochar coating blends had a substantial and positive impact on germination, seedling elongation, and fresh biomass in okra. They hypothesized that since biochar is a carbonaceous organic matter and a source of abundant nutrients, it could result in an increase in plant growth and biomass accumulation by supplying rich nutrition to the seedling embryo during emergence.…”
Section: Discussionsupporting
confidence: 78%
“…[9]. Previous studies have documented that biochar includes smoke-derived substances and growth-promoting compounds, which emit potent chemical signals, facilitating emergence and plant establishment via the enhancement of soil texture and moisture retention ability [13,14]. Furthermore, evidence from field trials has confirmed that biochar as a seed coating agent is favorable for improving rice emergence rate and stand establishment, ultimately maximizing grain yield [9,11] reviewed the literature extensively and concluded that the promotion of stand establishment may be due to the high porosity and large surface area of biochar, which enhances water availability and rich nutrients around the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the scarcity of improved seeds. The limited availability of high‐quality seed and, if available, high seed prices of UUCs, such as Bambara groundnut (Muhammad et al., 2020), pearl millet (Revoredo‐Giha et al., 2022), okra (Adelabu & Franke, 2022), sesame, taro mustard, bottle gourd, sorghum, amaranths, and others (Parihar et al., 2010; Tadele, 2019), is a major issue. Furthermore, poor seed performance and low seed quality limit the expansion of cultivated land.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review of prior studies of biochar-based seed coatings located 10 publications presenting data for 42 comparisons suitable for meta-analysis [25][26][27][42][43][44][45][46][47][48], plus 5 comparisons from the present study. PVAc was the single most common binding agent represented in the data (4 of 11 studies).…”
Section: Meta-analysis Of Pvac Effects On Germination Of Biochar-coat...mentioning
confidence: 99%